Effectiveness of lockdown as COVID-19 intervention: official and computed cases in Nepal - Bhandary, Shital (Journal of Patan Academy of Health Sciences, 2020)
Introduction: COVID-19 was first reported on 31 December 2019 from China. It was first confirmed in Nepal on 23 January 2020. Government enforced first wave of nationwide ‘lockdown’ for one week on 24 March 2020 and fourth from 16 April for 12 days. This paper aims to compute effectiveness of lockdown on COVID-19 cases in Nepal. Method: Doubling times were calculated using official COVID-19 records first, and then, the number of COVID-19 cases based on various doubling time scenarios staring 23 January 2020 were computed and compared with the official cases of Nepal. All the calculations were done in Microsoft Excel. Result: Doubling time was 60-day between first and second case, 5-day between 2nd and 5th, 15-day between 5th and 12th and again 5-day between 12th to 30th cases. Doubling time increased to 15-day after the lockdown. Estimated doubling time was 28 days till March, 21 days till 12 April and 18 days till 17 April 2020 and it is expected to reach 15 days on 24 April 2020. Conclusion: The reported COVID-19 cases doubling time was 5, 15 and 5 days in Nepal after the lockdown. The doubling time increased due to lockdown.